Intralesional therapy for metastatic melanoma. (December 2014) - Sloot, Sarah; Rashid, Omar M; Zager, Jonathan S
<x xml:space="preserve">Abstract</x> Introduction: Intralesional therapy for metastatic melanoma has some advantages over systemic therapy. Local drug administration allows for delivery of an increased concentration of the agent and reduced systemic exposure, thereby increasing local efficacy and limiting toxicity. Moreover, since in vivo tumor nodules contain the tumor antigens, this tumor tissue may serve as an autologous vaccine to induce systemic immunity. This so-called 'bystander effect', where uninjected distant lesions exhibit a response, has been reported in select intralesional therapy trials. Areas covered: This review will give an overview of the working mechanisms, clinical evidence and side effects for available intralesional and topical therapies and summarize the most recent developments in this field. Expert opinion: The ideal treatment approach for locoregionally advanced melanoma should be multidisciplinary and tailored to the patient, taking into consideration patient-related, tumor-related factors (such as location, tumor burden, mutation status) and previous treatments received. It will likely not be a single therapy, but rather a combination of injectable treatments, regional perfusions and systemic therapies.